Experimental investigation of the effect of fatty acids configuration, chain length, branching and degree of unsaturation on biodiesel fuel properties obtained from lauric oils, high-oleic and high-linoleic vegetable oil biomass - Adewale Johnson Folayan; Paul Apeye Lucky Anawe; Adeyemi Emman Aladejare; Augustine Omoniyi Ayeni (Energy Reports, 2019)
A very good understanding of the structure, level, type and physical property relationships of fatty acids in plants oils and their methyl esters (FAMEs) is of utmost importance when selecting vegetable oils for a particular desired biodiesel quality that meets the operating condition requirements of the compression-ignition diesel engine and the climatic dictate of the environment under which the engine is operated. It is on this premise that the degree of influence of fatty acid configuration, chain length, branching and unsaturation on cold flow and critical properties of biodiesel was investigated. The critical properties studied include: saponification and cetane number, iodine value, higher heating values, density, flash point and kinematic viscosity. The feed stock consists of three groups of vegetable oil biomass. The group one is made up of highly saturated, lauric coconut and palm kernel oils while group two consists of high linoleic, soyabean and corn oil biomass with low percentage of mono-unsaturated and high percentage of poly-unsaturated fatty acid. High oleic olive and canola oil constituted the third group of biomass. The triglycerides in these oils were converted to methyl esters by alkali-catalyzed transesterification reaction under standard conditions. The fatty acid methyl esters (FAMEs) compositional analyses of these feed stocks was done by using Agilent, HP 6890 Gas Chromatograph equipped with Flame ionization detector and 6890 Auto Sampler that connects with a controller box (GC-FID). The various biodiesel cold flow behaviour and critical properties under investigation were evaluated by the American society for testing materials (ASTM D6751-07b) and the European union (EN 14214) standard procedures and techniques. Better cold flow behaviour was exhibited by biomass with higher degree of unsaturation, longer chain length, higher degree of branching and with cis configuration. While critical properties showed a lot of variations based on fatty acid profile.
Keywords: 330; Biomass; Branching; Chain length; Cold flow behaviour; Critical properties; Gas chromatography; Transesterification reaction; Unsaturation